AKUNTANSI UNTUK PEMAIN SEPAK BOLA - Devi, Astri Prima (UI Scholars Hub, 2004)
Accounting reports on intangible assets have long been a problem, especially, those related to human capitals. They have become a problem whether they appear in balance sheet or not. These human capitals have to fulfill asset definitions and recognition criteria. This paper highlights human capital reported in the United Kingdom football club’s balance sheet. As we know the United Kingdom football industries have developed and yielded hundred billions pounds every year. They have also made football players become most important and most expensive in football clubs, with clubs paying regular large transfer fees in the transfer market to acquire players. FRS 10 Accounting for intangible assets and goodwill, recommends capitalization as the most appropriate treatment for intangible assets. There are two main issues that will be analyzed in this paper. First, do football players fulfill the accounting criteria to be classified as assets of the football clubs? Second, if so how should they account for?